Reduction of Brachiaria plantaginea infestation on soybean crop with black oat residues - Theisen, Giovani; Vidal, Ribas Antonio; Fleck, Nilson Gilberto (Pesquisa Agropecuaria Brasileira, 2000)
This work was conducted at Universidade Federal do Rio Grande do Sul, in Eldorado do Sul, Rio Grande do Sul State, Brazil, during 1996/97, to evaluate the effect of black oats (Avena strigosa Schreb.) residues on alexandergrass (Brachiaria plantaginea (Link) Hitch.) density and on soybean (Glycine max L. Merrill) yield. Treatments were arranged in split-plot in a randomized complete block design with four replicates, with weed control method as main plots and level of black oat residues as subplots. An exponential reduction of alexandergrass density was observed, with data varying from 829 to 86 plants/m2 for levels of straw on the soil surface of 0 to 10.5 ton/ha, respectively. Higher weed infestation occurred on the crop row than between the rows. In the weed-free treatments, soybean yield was not affected by crop residues. On the other hand, soybean yield increased linearly with increased amount of black oat residues on the soil controlling the weed. In weedy areas, soybean yield increased at the rate of 158 kg/ha for each ton of straw on the soil surface.